Healthcare-associated Infections at a Tertiary Level Pediatric Intensive Care Unit From Turkey - Gülhadiye Avcu; Başak Yıldız Atıkan (Galenos Yayinevi, 2021)
Aim:Healthcare-associated infections are important conditions, as they may increase morbidity and mortality, prolong hospital stay and increase costs. A higher incidence of healthcare-associated infections has been reported in developing countries, but data on its epidemiology in pediatric patients are limited. The aim of this study was to determine the rate and distribution of health care-associated infections and antimicrobial susceptibility patterns in a pediatric intensive care unit.Materials and Methods:Demographic and clinical details, microbiological findings, antibiotic susceptibility results and the outcomes of all hospitalized pediatric intensive care unit patients were collected for one year (September 2017 to September 2018). Results:The health care-associated infections rate was 5.6 per 100 admissions and the incidence density was 7.2 per 1,000 patient-days. Bloodstream infections (50%) were the most common type and Klebsiella species (40.9%) was the most common cause of health careassociated infections. All of the Klebsiella spp. were resistant strains producing extended-spectrum beta-lactamases (77.7%) and the remaining were resistant to carbapenem. Acinetobacter species and colistin resistance was not detected in any isolates.Conclusion:This study demonstrated a low prevalence of health care-associated infections but a high rate of antibiotic resistance in Klebsiella species in a pediatric intensive care unit. In addition to improved surveillance, consultation with infectious disease specialists will allow the development of interventions to reduce healthcare-associated infections, in order to regulate both empirical treatment and ongoing management, and also to provide appropriate targeted therapy.